Destabilization of the human epigenome: consequences of foreign DNA insertions - Weber, Stefanie; Hofmann, Andrea; Herms, Stefan; Hoffmann, Per; Dörfler, Walter (Epigenomics, 2015)
We previously reported changes of DNA methylation and transcription patterns in mammalian cells that carry integrated foreign DNA. Experiments were now designed to assess the epigenetic consequences of inserting a 5.6 kbp plasmid into the human genome.Differential transcription and CpG methylation patterns were compared between transgenomic and nontransgenomic cell clones by using gene chip microarray systems.In 4.7% of the 28.869 gene segments analyzed, transcriptional activities were up- or downregulated in the transgenomic cell clones. Genome-wide profiling revealed differential methylation in 3791 of > 480,000 CpG's examined in transgenomic versus nontransgenomic clones.The data document genome-wide effects of foreign DNA insertions on the epigenetic stability of human cells. Many fields in experimental biology and medicine employ transgenomic or otherwise genome-manipulated cells or organisms without considering the epigenetic consequences for the recipient genomes.
EVALuna2:8268